Fungsi Hasil Laboratorium Forensik Sebagai Bukti dalam Tindak Pidana Narkotika - Farid, Achmad Miftah; Indahsari, Novi Nur (Universitas Semarang, 2024)
This research aims to examine the position of forensic laboratory analysis results within the legal system based on Law Number 35 of 2009 concerning Narcotics, and the function of forensic laboratory results as evidence in narcotics criminal cases at the Sukoharjo Police Resort. The forensic laboratory plays an important role in proving narcotics cases, including in the Sukoharjo Police Resort area, by ensuring the identification of the type and concentration of narcotics as valid evidence in court. Unlike previous studies, the focus of this research is on the validity of forensic evidence in supporting justice in narcotics cases, particularly in the Sukoharjo area. The research method used is normative juridical with an analytical approach to relevant legislation, as well as using primary data from Law Number 35 of 2009, the Criminal Procedure Code, and the Police Medical Regulations. Research findings indicate that forensic laboratories play a central role in proving drug-related crimes by providing valid scientific analysis, which also influences judges' considerations in the criminal justice system. Law Number 35 of 2009 has provided a clear legal basis, but the validity of forensic laboratory results can be questioned if there is damage or contamination of the evidence. This study highlights the importance of more optimal forensic evidence management at Sukoharjo Police Station and recommends the enhancement of quality control procedures to minimize these obstacles in order to ensure justice and legal certainty. Artikel ini bertujuan untuk mengkaji kedudukan hasil analisis laboratorium forensik dalam sistem hukum berdasarkan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika, serta fungsi hasil laboratorium forensik sebagai alat bukti dalam kasus tindak pidana Narkotika di Kepolisian Resor Sukoharjo. Laboratorium forensik memiliki peranan penting dalam pembuktian perkara Narkotika, termasuk di wilayah Polres Sukoharjo, dengan memastikan identifikasi jenis dan kadar Narkotika sebagai alat bukti yang sah di pengadilan. Berbeda dari penelitian sebelumnya, fokus kajian ini adalah validitas bukti forensik dalam mendukung keadilan kasus Narkotika, terutama di kawasan Sukoharjo. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan analisis terhadap peraturan perundang-undangan yang relevan, serta menggunakan data primer dari Undang-Undang Nomor 35 Tahun 2009, KUHAP, dan Peraturan Kedokteran Kepolisian. Temuan penelitian menunjukkan bahwa laboratorium forensik memiliki peran sentral dalam pembuktian tindak pidana Narkotika melalui penyediaan analisis ilmiah yang valid, yang turut memengaruhi pertimbangan hakim dalam sistem peradilan pidana. Undang-Undang Nomor 35 Tahun 2009 telah memberikan landasan hukum yang jelas, namun validitas hasil laboratorium forensik dapat diragukan jika terjadi kerusakan atau kontaminasi pada barang bukti. Kajian ini menyoroti pentingnya pengelolaan bukti forensik yang lebih optimal di Polres Sukoharjo, serta merekomendasikan peningkatan prosedur pengendalian kualitas untuk meminimalkan hambatan tersebut demi menjamin keadilan dan kepastian hukum.